Multimodal “sensory illusions” for improving spatial awareness in virtual environments - Lawson, Glyn; Roper, Tessa; Abdullah, Che (2016)
Inaccurate judgement of distances in virtual environments (VEs) restricts their usefulness for engineering development, in which engineers must have a good understanding of the spaces they are designing. Multimodal feedback can improve depth perception in VEs, but this has yet to be implemented and tested in engineering applications with systems which provide haptic feedback to the body.